The role of Zakat and Fitrah in improving Community Welfare: A Case Study of Baznas Garut Regency - Enceng Iip Syaripudin; Ah. Fathonih; Ija Suntana; Ayi Yunus Rusyana; Gini Gaussian; Deni Kon Kon Furkony (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Zakat has great potential to improve the welfare of people in Indonesia, including in Garut Regency. The professional and accountable management of zakat by the National Zakat Agency (BAZNAS) of Garut Regency is expected to encourage an increase in the economic welfare of the community. However, the performance of BAZNAS Garut in this case is not optimal, so the impact on improving public welfare is also not optimal. This gives rise to a critical perspective in society. This study aims to analyze the governance, distribution system, and the impact of Zakat mal and Zakat fitrah distributed BAZNAS Garut in improving the economic welfare of the community. The method used is descriptive analysis with empirical juridical approach and graphic simulation. The results showed that: 1) conceptually and empirically, zakat can increase economic growth and welfare; 2) distribution of zakat Mal BAZNAS Garut consists of consumptive and productive programs; 3) zakat mal has a positive impact on improving economic welfare; and 4) zakat al-Fitr also has a positive impact on improving the economic welfare of the community. However, this study concludes that the management of zakat by BAZNAS Garut is not optimal, so it is necessary to improve performance to realize better welfare.